Effect of High (200 μg/kg per Minute) Adenosine Dose Infusion on Fractional Flow Reserve Variability. Issue 11 (November 2016) - Alexopoulos, Dimitrios; Xanthopoulou, Ioanna; Tsigkas, Grigorios; Koutsogiannis, Nikolaos; Salata, Paraskevi; Armylagos, Stylianos; Moulias, Athanasios; Davlouros, Periklis
Abstract : Background: Variations in distal coronary pressure (Pd)/aortic pressure (Pa) ratio during steady‐state hyperemia with standard (140 μg/kg per minute) adenosine dose may hamper accurate fractional flow reserve assessment. This study investigated to what extent an increased adenosine dose can overcome Pd/Pa variation. Methods and Results: In a prospective, single‐arm study, out of 95 prospectively screened patients, 38 (40.0%) exhibited significant (≥0.05 difference of max Pd/Pa minus min Pd/Pa) variations in Pd/Pa from 15 s post Pd/Pa dip and until the end of a 3‐minute adenosine (140 μg/kg per minute) infusion. Thirty patients agreed to participate in a post 5‐minute repeat fractional flow reserve assessment using 200 μg/kg per minute 3‐minute adenosine infusion. The study's co‐primary end point of Pd/Pa coefficient of dispersion was lower for the high versus standard adenosine dose: 1.31 (1.13–2.72) versus 2.76 (2.38–5.60), P =0.002. The study's co‐primary end point of ΔPd/Pa was also lower for the high versus standard adenosine dose: 0.065 (0.038–0.10) versus 0.08 (0.06–0.11), P =0.002. This difference was mainly driven by the lowering effect of the high adenosine dose on the maximum Pd/Pa compared to the standard dose: 0.84 (0.81–0.93) versus 0.90 (0.83–0.95), P =0.007, while minimum Pd/Pa remained unaffected. High adenosine dose was adequately tolerated by all patients, without requiring infusion discontinuation in any case. Conclusions: Pd/Pa variability is frequently observed during standard adenosine infusion and is significantly decreased following a high (200 μg/kg per minute) adenosine dose. This is achieved without a significant difference in the minimum Pd/Pa. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02350439.